2009
DOI: 10.2174/1871520610909040457
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Actions of Omega-3 Fatty Acids - Current State and Future Perspectives

Abstract: Omega-3 fatty acids (omega3-FA) were shown to attenuate growth and induce apoptosis in a variety of human cancer cell lines derived from colonic, pancreatic, prostate, and breast cancer. In addition, recent findings indicate that omega3-FA act synergistically with chemotherapeutic agents and may also be used to enhance tumour radiosensitivity. The mechanisms underlying the anti-tumour effects of omega3-FA are complex. Incorporation of omega3-FA in biological membranes alters the profile of lipid mediators gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 0 publications
1
61
0
2
Order By: Relevance
“…A recent study by Schwerbrock and colleagues (40) showed that FO feeding had deleterious effects on the immune response to influenza infection, which was characterized by decreased CD8 + cytotoxic T lymphocytes, reduced neutrophils at the site of infection, and impaired natural killer cell cytotoxicity. Taken together, these observations indicate that whereas FO supplementation may be beneficial in lowering the risk of some cancers (41), FO may act differently in the etiology of infection-associated cancers.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study by Schwerbrock and colleagues (40) showed that FO feeding had deleterious effects on the immune response to influenza infection, which was characterized by decreased CD8 + cytotoxic T lymphocytes, reduced neutrophils at the site of infection, and impaired natural killer cell cytotoxicity. Taken together, these observations indicate that whereas FO supplementation may be beneficial in lowering the risk of some cancers (41), FO may act differently in the etiology of infection-associated cancers.…”
Section: Discussionmentioning
confidence: 78%
“…At least partly due to their antiinflammatory properties, omega-3 (w-3) fatty acids are proposed to have anticancer actions (2). Indeed, once incorporated into biologic membranes, w-3 fatty acids are converted into lipid mediators, named eicosanoids, with anti-inflammatory properties via a succession of enzymes: desaturase, elongase, cyclooxygenase, and lipoxygenase (3).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence from animal and in vitro studies indicates that fatty acids, especially the long-chain polyunsaturated fatty acids (PUFAs), 2 affect carcinogenesis (1). n-3 PUFAs inhibit the growth of tumor cells both in vivo and in vitro (2,3), decrease metastasis and cachexia (4,5), and increase the cytotoxic effects of some chemotherapeutic agents (6), although the results are not always consistent (7,8).…”
mentioning
confidence: 99%
“…n-3 PUFAs inhibit the growth of tumor cells both in vivo and in vitro (2,3), decrease metastasis and cachexia (4,5), and increase the cytotoxic effects of some chemotherapeutic agents (6), although the results are not always consistent (7,8). In addition, n-3 PUFAs reduce cell proliferation and induce differentiation and apoptosis in hepatocarcinoma and leukemia cells (9 -12).…”
mentioning
confidence: 99%
See 1 more Smart Citation